Evaluation of Mombaça grass (Panicum maximum Jacq.) under two different nitrogen rates - Freitas, Karina Rocha (2008)
The purpose of this experiment was to evaluate the effect of different rates of N on dry matter production of Mombaça grass (Panicum maximum Jacq.), the efficiency of nitrogen conversion and nutrient concentration contained in plant tissue . Four rates of N were used (70, 140, 210 and 280 kg/ha/year) as Urea form. The evaluation period was from November of 2002 to April of 2003, when six cuts of 28 days intervals and 30 cm high from the soil were accomplished. The statistical design used was a completely randomized block, in split spot parcel in time, with eight replications. Scott-Knott test was used for average comparison. The best dry matter productions were obtained with application of 280 kg of N/ha. The highest efficiencies of the conversion were verified by the application of the lower doses of N.